Implementasi Actuating Dalam Manajemen Bisnis Syariah Dalam Operasional Usaha Tahu Modern Di Telang Kamal Bangkalan - Galih Angga Mahendra; Retno Khabibatuni’mah; Khoyril Waro; Farihatus Sholihatus Syafiyah; Nuraida Sayyidati; Siti Zubaidah (Faculty of Economics and Business Universitas Dian Nuswantoro, 2025)
Micro, small and medium enterprises (MSMEs) represent a significant segment of the Indonesian economy and serve as a conduit for the implementation of sharia values in business practices. The present study aims to examine the implementation of the actuating function in sharia business management at Tahu Modern in Telang Kamal, Bangkalan. The research method employed is qualitative, with a case study approach. The data was obtained through a combination of interviews, observations, and documentation, and was then analysed thematically based on four indicators: the principle of tauhid, Islamic communication, product quality and halalness, and sharia marketing strategies. The findings indicate that the concept of tauhid is operationalised through the business owner's consistent implementation of worship, the manifestation of Islamic communication through a cordial and truthful demeanour towards customers, the maintenance of product quality through the selection of reliable raw materials, and the execution of sharia marketing in a straightforward yet efficacious manner through the utilisation of Google Maps and the provision of bonuses for loyal customers. These findings indicate that the success of MSMEs is not solely determined by financial profits, but also by the integration of Islamic values into business operations. This study makes a significant academic contribution to the extant literature on sharia management, while concurrently providing practical inspiration for MSMEs to enhance their competitiveness whilst maintaining the principle of blessing. Usaha mikro, kecil, dan menengah (UMKM) merupakan sektor penting dalam perekonomian Indonesia sekaligus sarana penerapan nilai-nilai syariah dalam praktik bisnis. Penelitian ini bertujuan untuk mengkaji implementasi fungsi actuating dalam manajemen bisnis syariah pada usaha Tahu Modern di Telang Kamal, Bangkalan. Metode yang digunakan adalah penelitian kualitatif dengan pendekatan studi kasus. Data diperoleh melalui wawancara, observasi, dan dokumentasi, kemudian dianalisis secara tematik berdasarkan empat indikator: prinsip tauhid, komunikasi Islami, kualitas dan kehalalan produk, serta strategi pemasaran syariah. hasil penelitian menunjukkan bahwa prinsip tauhid terimplementasi melalui konsistensi ibadah pemilik usaha, komunikasi Islami tampak dalam sikap ramah dan jujur terhadap pelanggan, kualitas produk dijaga dengan pemilihan bahan baku terpercaya, dan pemasaran syariah dilakukan secara sederhana namun efektif melalui pemanfaatan Google Maps serta pemberian bonus bagi konsumen setia. Temuan ini menegaskan bahwa keberhasilan UMKM tidak hanya ditentukan oleh keuntungan finansial, tetapi juga oleh integrasi nilai-nilai Islam dalam operasional usaha. Penelitian ini memberi kontribusi akademik bagi literatur manajemen syariah sekaligus menawarkan inspirasi praktis bagi UMKM agar mampu meningkatkan daya saing dengan tetap menjaga prinsip keberkahan